2011
DOI: 10.1088/0951-7715/25/1/165
|View full text |Cite
|
Sign up to set email alerts
|

Almost-additive thermodynamic formalism for countable Markov shifts

Abstract: We introduce a definition of pressure for almost-additive sequences of continuous functions defined over (non-compact) countable Markov shifts. The variational principle is proved. Under certain assumptions we prove the existence of Gibbs and equilibrium measures. Applications are given to the study of maximal Lypaunov exponents of product of matrices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…Remark 5.2. Theorem 5.1 generalizes [IY1,Theorem 4.1] in which almost-additive Bowen sequences on finitely primitive countable Markov shifts are considered. If G = {log g n } ∞ n=1 is an almost-additive Bowen sequence, then…”
Section: Invariant Gibbs Measures and Uniqueness Of Gibbs Equilibriummentioning
confidence: 84%
See 3 more Smart Citations
“…Remark 5.2. Theorem 5.1 generalizes [IY1,Theorem 4.1] in which almost-additive Bowen sequences on finitely primitive countable Markov shifts are considered. If G = {log g n } ∞ n=1 is an almost-additive Bowen sequence, then…”
Section: Invariant Gibbs Measures and Uniqueness Of Gibbs Equilibriummentioning
confidence: 84%
“…In all these cases, it was shown that the definition does not depend on the symbol a chosen. The Gurevich pressure was defined and studied for almostadditive sequences on topologically mixing countable Markov shifts by Iommi and Yayama [IY1]. We stress that the definition given here extends both the class of sequences of potentials and the class of shifts (satisfying the weak specification) previously considered in the literature.…”
Section: 2mentioning
confidence: 88%
See 2 more Smart Citations
“…Our approach uses ideas from the non-additive thermodynamical formalism and we estimate the measure of deviation sets in the case that the reference measure satisfies a weak Gibbs property. Some recent results considering the thermodynamical formalism of almost additive or sub-additive sequences of potentials include [4,19,20,22,29]: in all cases the authors proved that there exists a unique equilibrium state µ and it is absolutely continuous with respect to a Gibbs measure ν with density bounded away from zero and infinity. Building on [3], Méson and Vericat [28] obtained bounds for large deviations processes for a family of non-additive potentials = {ϕ n }, namely those such that ϕ n − ϕ n−1 • f converge uniformly.…”
Section: Introductionmentioning
confidence: 99%